Potensi Interaksi Obat Antipsikotik Pada Pasien Skizofrenia Dewasa Di Instalasi Rawat Inap Rumah Sakit Jiwa Daerah Dr. Rm. Soedjarwadi Periode Oktober - Desember Tahun 2015 - Manggalawati, Pratiwi; , Dra. Nurul Mutmainah, M.Si, Apt (2016)
Schizophrenia is categorized as a severe mental illness. The indicated symptoms are such as delusions, hallucinations and agitation. This research was done to find out the potential drug interactions of antipsychotic that occur in the adult patients of schizophrenia and the mechanisms of the interaction significance level of antipsychotic drugs in the adult patients of schizophrenia at inpatients installation RSJD Dr. RM. Soedjarwadi from October to December 2015. This research was an observational research which was done by using descriptive analysis. The data was taken by retrospective technique. This research was done by analyzing the medical data records of the patient. Based on the hospital policy, it is only allowed to take sample in the 3 months period from October to December 2015 then it was obtained 123 samples of the patients with schizophrenia who underwent hospitalization and antipsychotic medication therapy. The samples obtained in this research were the hospitalized schizophrenic patients who were selected by using inclusion criteria. There were 68 patients who met the criteria. Based on the results of the study, it was concluded that the antipsychotic drugs which widely used haloperidol (61.8%), trifluoperazine (42.6%), and risperidone (42.6%). Based on the mechanism result of 235 potential interactions, found pharmacokinetic interaction at 41 cases (17,44%) and the interaction of the pharmacodynamic mechanism occurs at 194 cases (82,56%), Meanwhile, result based on the side effects term showed that there are 235 potential interactions, 214 potential significant interaction (91.07%), and 21 potential serious interaction (8.93%).